The Role of Liquid Biopsies in Early Cancer Detection and Monitoring - Kirolos Eskandar (Indonesian Society for Cancer Chemoprevention, 2025)
Liquid biopsies have emerged as a transformative tool in oncology, offering a minimally invasive method for early cancer detection and real-time monitoring of disease progression. This literature review explores the technological advancements and clinical applications of liquid biopsies, focusing on their role in detecting circulating tumor cells (CTCs), cell-free DNA (cfDNA), and other biomarkers. We examine the efficacy of liquid biopsies in early cancer screening, their potential for monitoring treatment response, and their ability to detect recurrence and metastasis. Despite the promising applications, challenges such as technical limitations, biological variability, and cost-effectiveness must be addressed to fully integrate liquid biopsies into routine clinical practice. The future of liquid biopsies looks promising, with emerging trends in multi-omic approaches and artificial intelligence paving the way for more personalized and effective cancer care. This review included 34 peer-reviewed studies identified through a systematic PRISMA-guided search across four databases.Keywords: Liquid Biopsies, Early Cancer Detection, Circulating Tumor Cells (CTCs), Cell-Free DNA (cfDNA), Cancer Monitoring, Multi-omics, Artificial Intelligence in Cancer Diagnostics, Real-time Monitoring.